Soy foods and nuts consumption during early pregnancy are associated with decreased risk of gestational diabetes mellitus: a prospective cohort study. (12th December 2022) - Pang, Xinxin; Cai, Congjie; Dong, Hongli; Lan, Xi; Zhang, Yiqi; Bai, Dan; Hao, Lixin; Sun, Hong; Li, Fei; Zeng, Guo
Abstract: Aims: To study the relationship of soy foods and nuts consumption during early pregnancy with the risk of gestational diabetes mellitus (GDM). Methods: This was a prospective observational study conducted in Southwest China. Dietary information was assessed through 3-day 24-h dietary recalls at 6–14 gestational weeks. For soy foods and nuts, non-consumers were used as the reference category and the consumers were categorized into tertiles. GDM was assessed with the 75-g, 2-h oral glucose tolerance test at 24–28 gestational weeks. Log-binomial models were used to assess the effects of soy foods and nuts on GDM. Results: Of the 1495 pregnant women, 529 were diagnosed with GDM. Median (IQRs) intakes of soy foods and nuts were 2.9 (0.0, 10.3) and 5.0 (0.0, 15.0) g/d, respectively. Our study found that, compared with the non-consumers, the highest tertile of soy foods intake was associated with a decrease in risk of GDM (RR = 0.73, 95%CI: 0.54–0.99, p = .049). Similarly, compared with the non-consumers, a negative relationship between the highest tertile of nuts intake and GDM risk was identified (RR = 0.65, 95%CI: 0.48–0.89, p = .007). Conclusions: Consumption of soy foods and nuts are independently inversely associated with the risk of GDM during early pregnancy.